ANTESEDEN DARI NIAT PERILAKU PEMBELIAN PRODUK RAMAH LINGKUNGAN - Prahasta, Giri; Pratomo, Luki Adiati (Jurnal Manajemen, 2016)
This research aims to examine the effect of consumers attitude toward the protection of the environment, personal norms related to green issues, and consumers willingness to pay for green product attributes on the intention to green purchasing behavior . The data was gathered by using questionnaires and was collected from 153 respondents who had bought organic food in Jakarta. The sampling technique used is purposive sampling. Mutiple Regression is used to analyze the data. The findings showed that those antecedences of intentions to green purchasing behavior that consists of the consumers attitude toward the protection of the environment, personal norms related to green issues, and consumers willingness to pay for green product attributes have positive influence on intention to green purchasing behavior. For future research it is suggested to research other green products in addition to organic food products and add other variables.Keywords: Attitude toward the protection of the environment, Intention to green purchasing behavior